Do lagoons near concentrated animal feeding operations promote nitrous oxide supersaturation? - Makris, Konstantinos C.; Sarkar, Dibyendu; Andra, Syam S.; Bach, Stephan B H; Dattad, Rupali K. (My University, 2009)
Animal wastewater lagoons nearby concentrated animal feeding operations (CAFOs) represent the latest tendency in global animal farming, severely impacting the magnitude of greenhouse gas emissions, including nitrous oxide (N2O). We hypothesized that lagoon wastewater could be supersaturated with N2O as part of incomplete microbial nitrification/denitrification processes, thereby regulating the N2O partitioning in the gaseous phase. The objectives of this study were: (i) to investigate the magnitude of dissolved N2O concentrations in the lagoon; and (ii) to determine the extent to which supersaturation of N2O occurs in wastewater lagoons. Dissolved N2O concentrations in the wastewater samples were high, ranging from 0.4 to 40.5 μg N2O mL−1. Calculated dissolved N2O concentrations from the experimentally measured partition coefficients were much greater than those typically expected in aquatic systems (<∼0.6 μg N2O mL−1). Knowledge of the factors controlling the magnitude of N2O supersaturation could potentially bridge mass balance differences between in situ measurements and global N2O models.
Keywords: Supersaturation; Nitrous oxide; Climate change; Global warming; Animal waste; Lagoons; Wastewater